The role of GTP-binding proteins in mechanochemical movements of microorganisms and their potential to form filamentous structures - Mikulík, K (Folia microbiologica, 1998)
Prokaryotic cells contain proteins which form extended chains or multimers that oscillate between monomers and oligomers of varying length. Hydrolysis of nucleoside triphosphates combined with site-specific disposition of substrates and products to monomers and multimers is the driving force of dynamic instability of these molecules. Polymeric structures are connected in some manner to a variety of signaling systems that adhere to the polymeric matrix, including the GTP-binding protein(s), protein kinases and phosphatases, and other proteins or systems that communicate between the cytoplasmic membrane and the cytosol. Flexible organization allowing regulated dynamic movement is one of the key elements in all living cells. In eukaryotic cells actin and tubulin are the two main components of dynamically controlled spatial system. These proteins are noteworthy for their ability to polymerize, reversibly, into filaments or microtubules in association with hydrolysis of ATP or GTP, respectively. As such, they regulate most of the mechanics of cell movement including cell division, cell differentiation, phagocytosis and other dynamic phenomena. Recent evidence revealed that microbial cells create functional domains at specific sites of the cells and can form cytoplasmic tubules and fibers.
Keywords: proteiny vázající GTP; Bacterial Physiological Phenomena; fyziologie bakterií; pohyb; Bacteria; Phosphorylation; Microtubules; GTP-Binding Proteins; mikrotubuly; Bacterial Proteins; Polymers; Tubulin; Cytoskeletal Proteins; cytoskeletální proteiny; Movement; fosforylace; tubulin; polymery; bakteriální proteiny